Peran Sistem Informasi Akuntansi dalam Mewujudkan Efektivitas Audit Persediaan - Nur Afifah Syam; Nurawalia Pratiwi; Mahsyuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the role of Accounting Information Systems in enhancing the effectiveness of inventory audits. Inventory represents a critical asset with a high risk of misstatement and misappropriation, requiring accurate information and strong internal control to support audit activities. The implementation of an integrated Accounting Information System enables companies to record, process, and present inventory data systematically and reliably. High-quality systems provide accurate, timely, and verifiable information that facilitates audit procedures, strengthens internal control evaluation, and supports audit evidence collection. The findings indicate that Accounting Information Systems contribute significantly to improving audit efficiency, reducing the risk of inventory discrepancies, and enhancing audit reliability. Moreover, the system supports fraud prevention through better transaction transparency and traceability. This study confirms that companies with well-implemented Accounting Information Systems tend to achieve more effective inventory audits. The results are expected to provide practical insights for management in optimizing accounting systems and contribute to the development of accounting and auditing literature related to inventory management.